V Congress of Neurosurgeons of Ukraine (June 25–28, 2013, Uzhgorod) and Plenum of the Board of the Ukrainian Association of Neurosurgeons (November 29, 2013, Kyiv) - Smolanka, Volodymyr; Voznyak, Oleksandr; Huk, Andriy; Pedachenko, Eugene (Ukrainian Neurosurgical Journal, 2014)
No abstract.